2021
DOI: 10.1136/bmjopen-2020-047296
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability of a school-based health intervention for prevention of non-communicable diseases in marginalised communities: protocol for a mixed-methods cohort study

Abstract: IntroductionThe prevalence of chronic, lifestyle-related diseases is increasing among adults and children from low-income and middle-income countries. Despite the effectiveness of community-based interventions to address this situation, the benefits thereof may disappear in the long term, due to a lack of maintenance, especially among disadvantaged and high-risk populations. The KaziBantu randomised controlled trial conducted in 2019 consisted of two school-based health interventions, KaziKidz and KaziHealth. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Therefore, school-aged twins are considered a desirable group of twins in registries. School-based health promotion interventions (HPIs) have been widely used to promote physical and mental health in school children 45 46. Implementing WHO-recommended HPSs can integrate and coordinate a more efficient system for the healthy child development of students affected by HPIs 47–49.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, school-aged twins are considered a desirable group of twins in registries. School-based health promotion interventions (HPIs) have been widely used to promote physical and mental health in school children 45 46. Implementing WHO-recommended HPSs can integrate and coordinate a more efficient system for the healthy child development of students affected by HPIs 47–49.…”
Section: Discussionmentioning
confidence: 99%
“…This qualitative descriptive study is part of a mixed-methods project evaluating two school-based interventions: KaziKidz , a health promotion program for learners, and KaziHealth , a workplace health intervention for educators [ 25 ]. Both interventions were implemented in the context of a randomized controlled trial in eight participating schools, four intervention and four control, in 2019 [ 10 ].…”
Section: Methodsmentioning
confidence: 99%
“…The second section of Figure 1 shows that from an eligible sample of 543 children identified at risk, 280 were enrolled in the study and included in the final analysis (133 intervention versus 147 control arm). Further details on the study population and setting can be found in the study protocols (22,23). (24).…”
Section: Participantsmentioning
confidence: 99%